Evaluation of economic loss caused by Indian crested porcupine (Hystrix indica) in agricultural land of district Muzaffarabad, Azad Jammu and Kashmir, Pakistan - Ashraf,R. Z. (2023)
Abstract The Indian crested porcupine (Hystrix indica) is a vertebrate pest of agricultural lands and forest. The study was aimed to report the damage to local crops by the Indian crested porcupine (Hystrix indica) in the Muzaffarabad District. A survey was conducted to identify the porcupine-affected areas and assess the crop damage to the local farmers in district Muzaffarabad Azad Jammu and Kashmir (AJK) from May 2017 to October 2017. Around 19 villages were surveyed, and a sum of 191 semi-structured questionnaires was distributed among farmers. Crop damage was found highest in village Dhanni where a porcupine destroyed 175 Kg/Kanal of the crops. Regarding the total magnitude of crop loss, village Danna and Koomi kot were the most affected areas. More than half (51.8%) of the respondents in the study area suffered the economic loss within the range of 101-200$, and (29.8%) of the people suffered losses in the range of 201-300$ annually. Among all crops, maize (Zea mays) was found to be the most damaged crop ranging between 1-300 Kg annually. In the study area, porcupine also inflicted a lot of damages to some important vegetables, including spinach (Spinacia oleracea), potato (Solanum tuberosum) and onion (Allium cepa). It was estimated that, on average, 511Kg of vegetables are destroyed by porcupine every year in the agricultural land of Muzaffarabad. It was concluded that the Indian crested porcupine has a devastating effect on agriculture which is an important source of income and food for the local community. Developing an effective pest control strategy with the help of the local government and the Wildlife department could help the farmers to overcome this problem.